Pemanfaatan Tumbuhan Pangan oleh Masyarakat Talang Mamak di Taman Nasional Bukit Tigapuluh, Jambi - Francisca Murti Setyowati; Mangasa Hiras Siagian (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
An Ethnobotanical study was carried out on a group of Talang Mamak tribe of the Bukit Tigapuluh National Park, Jambi. The inter-relationship and the dependency of the tribe with the forest plant resources were reflected by their daily lives by gathering medicine and hunting. The tribe lives surroundings HPH of the Dalek Esa Raya Co. Ltd. A number of 92 plant species were used as their food. About 70% of the species recorded were gathered from the forests, and the rest (30%) were as cultivated plant. Various botanical aspects of each species with its usage and utilization methods were discussed.